Metode dan Corak Penafsiran Sayyid Qutb - Hafizzullah, Hafizzullah; Ismail, Nurhidayati (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
Interpretation of the Qur'an is one of the important fields of study in the science of interpretation, with various methods and patterns developed by the mufassir according to the context of their time. Sayyid Qutb, a prominent Muslim thinker, made a significant contribution through his work Fi Zilal al-Qur'an. This study focuses on the methods and patterns of interpretation used by Sayyid Qutb in his interpretation, by examining its characteristics, approaches, and implications for the understanding of the Qur'an in the modern era. This study aims to answer three main questions: (1) What is the interpretation method used by Sayyid Qutb in Fi Zilal al-Qur'an? (2) What are the patterns of interpretation that dominate the work? (3) How to apply it in the aspects of Aqidah, muamalah worship and morals. To answer this question, the research was carried out with a qualitative-descriptive approach, using the content analysis method of Sayyid Qutb's main work, and supported by the literature. . The results of the study show that this interpretation uses the Iqtirani tafsir method, which combines the tafsir bi al-ma'tsur method and tafsir bi al ra'yi, by using the tafsir tahlili method and the pattern (laun) of the interpretation is Al-adab wal ijtima'i, which is an interpretation that prioritizes literature and social society, the haraki pattern (movement) and also the Sufi style (isyari). Based on the explanation of the form of interpretation in the Tafsir Fî Zhilâlil Qur'an, it appears that in terms of Aqidah, Sayyid Qutb has a tendency to think of tasawwuf, while in interpreting verses related to worship and mu'amalah, such as zakat, and the prohibition of usury, Sayyid Qutb uses a social approach, by looking at social phenomena that occur in society, and finally, in understanding the verses about morality,  like understanding the meaning of uswatun hasanah, Sayyid Qutb tries to understand the meaning of the verse based on the context of the nuzul of the verse.